Effect of plant density on Stevia rebaudiana Bertoni water consumption - Pardini, A.; Paterniani, M.L.Stipp [UNESP]; Baldi, A.; Grassi, C.; Giunta, R.; Mugnai, E. (My University, 2010)
Stevia rebaudiana is a traditional crop of Latin America, now rising to international interest thanks to its specific glycosides that are very sweet and still poor of calories making its potential interesting for dietary recommendations. Its short growing cycle makes this species possible as an annual crop also in non tropical areas, including the Mediterranean Basin and parts of Italy, where rainfall or irrigation is available during late spring and summer. One of the main concerns is the quantity of water necessary for the crop and the ideal number of plants per hectare in order to maximize water use efficiency. The present research was carried out in central Italy to compare yields and water consumption in plots with three plant densities (50, 25, 16 plants per square metre). The results show that the most dense plots can give the best results in the area of the trial.
Keywords: Diet; Mediterranean; New crops; Stevia; Sugar; Stevia rebaudiana